Characteristics of patients with undiagnosed stage 3 chronic kidney disease: results from an observational study (REVEAL-CKD) in ChinaResearch in context - Sheng Nie; Shiyu Zhou; Claudia Cabrera; Shan Chen; Mengyun Jia; Shiyu Zhang; Licong Su; Qi Gao; Navdeep Tangri; Fan Fan Hou (The Lancet Regional Health. Western Pacific)
Summary: Background: Early diagnosis of chronic kidney disease (CKD) is crucial for timely intervention to delay disease progression and improve patient outcomes. However, data for clinical characteristics of Chinese patients with undiagnosed, early-stage CKD are lacking. Methods: REVEAL-CKD is a multinational, observational study using real-world data in selected countries to describe factors associated with undiagnosed stage 3 CKD, time to diagnosis, and CKD management post diagnosis. We analysed patient data from 20 hospitals in the China Renal Data System. Adult patients with two consecutive estimated glomerular filtration rate (eGFR) measurements indicating stage 3 CKD (30–<60 ml/min/1.73 m2) recorded >90–730 days apart from 2015 to 2020 were eligible. Findings: Among 35,222 eligible patients, 25,214 (71.6%) were undiagnosed (lacked a CKD diagnostic code before and up to six months post-second-qualifying-eGFR). Only 2344 (9.3%) undiagnosed patients eventually received a delayed diagnosis, whose median time to diagnosis was 18.1 (95% CI: 17.6–18.8) months. Age ≥65 years, being female, stage 3A CKD, and the absence of nephrology visit and comorbidities (diabetes, established cardiovascular disease, heart failure, hypertension, or chronic nephritic syndrome) were associated with undiagnosed CKD (P < 0.001). Among the diagnosed patients, the proportion receiving ≥1 prescription of guideline-recommended medications (e.g. renin-angiotensin system inhibitors) increased and their eGFR decline attenuated post-diagnosis. Interpretation: The high proportion of undiagnosed, early-stage CKD, and delayed diagnosis are concerning. The improved prescription patterns and the attenuation of eGFR decline post-diagnosis demonstrate the importance of early diagnosis and timely intervention in CKD patients. Funding: AstraZeneca China.